1999
DOI: 10.1007/s101200050017
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell infiltration around gastric cancer cells correlates with tumor angiogenesis and metastasis

Abstract: Abstract:Background. Increased numbers of mast cells are found in various solid tumors. To investigate the role of mast cells in the vicinity of gastric cancer cells, we used special staining and an immunohistochemical technique. Methods. Specimens were surgically obtained from 102 patients with gastric cancer. Mast cells around the tumor edge of gastric cancer nests were counted by staining with 0.05% toluidine blue solution. Blood vessels in these areas were also counted, by immunohistochemical staining of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 16 publications
3
92
0
4
Order By: Relevance
“…8 -11 Mast cells produce a broad repertoire of cytokines to regulate inflammatory responses, growth factors to stimulate blood vessels and fibroblasts, and enzymes capable of releasing growth factors from extracellular matrix. 5,8 -11,27,28,42 In other human tumors studies it has been shown that mast cell function is complicated with both pro -and antitumor effects, 35,[43][44][45][46] but to the best of our knowledge no studies have previously described differential roles of mast cells depending on the local microenvironment within the same clinical material. It is well established that inflammatory cell types within or surrounding tumors such as tumor-associated macrophages 47 and more lately also neutrophils 48 can be educated by growth factors and cytokines within the tumor microenvironment to acquire pro-or antitumor properties.…”
Section: Discussionmentioning
confidence: 99%
“…8 -11 Mast cells produce a broad repertoire of cytokines to regulate inflammatory responses, growth factors to stimulate blood vessels and fibroblasts, and enzymes capable of releasing growth factors from extracellular matrix. 5,8 -11,27,28,42 In other human tumors studies it has been shown that mast cell function is complicated with both pro -and antitumor effects, 35,[43][44][45][46] but to the best of our knowledge no studies have previously described differential roles of mast cells depending on the local microenvironment within the same clinical material. It is well established that inflammatory cell types within or surrounding tumors such as tumor-associated macrophages 47 and more lately also neutrophils 48 can be educated by growth factors and cytokines within the tumor microenvironment to acquire pro-or antitumor properties.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the findings in experimentally induced malignancies, some studies have suggested promote that mast cells tumour progression. For instance, mast cell infiltration correlates well with tumour angiogenesis and metastases in gastric cancer (Yano et al, 1999), colorectal cancer (Lachter et al, 1995), pulmonary adenocarcinoma (Takanami et al, 2000) and renal cell carcinoma (Tuna et al, 2006). In PCas, mast cell infiltration correlates with poor prognosis, suggesting that mast cells may promote tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MCs are involved and deregulated in number and phenotype in immune events and in several pathologies (20)(21)(22), including cancer (2,5,(8)(9)(10)12). Although it is widely accepted that these cells accumulate at the site of solid tumours and are able to modulate tumour behaviour, the functional role of each MC phenotype is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…By scanning the intratumoral zone and the invasive edge, we observed that the number of MCs of both phenotypes was significantly higher in the invasive edge than in the intratumoral zone in all Astler-Coller stages, with MCt being the prominent phenotype. The increased number of MCs in the invasive edge may be due to MC uninterrupted renewal from stem cells leaving blood vessels and beginning their differentiation into MCs in the connective tissue while migrating towards the tumour, most probably attracted by chemokines released into the tumoral microenvironment (8). In addition, MCs are located in connective tissue surrounding tumoral nests; the smaller the amount of connective tissue present in the intratumoral zone with respect to that in the invasive edge, the lower the number of MCs recorded in a determined area will be.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation